2017
DOI: 10.18632/oncotarget.16743
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides with selective antitumor mechanisms: prospect for anticancer applications

Abstract: In the last several decades, there have been significant advances in anticancer therapy. However, the development of resistance to cancer drugs and the lack of specificity related to actively dividing cells leading to toxic side effects have undermined these achievements. As a result, there is considerable interest in alternative drugs with novel antitumor mechanisms. In addition to the recent approach using immunotherapy, an effective but much cheaper therapeutic option of pharmaceutical drugs would still pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
243
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(252 citation statements)
references
References 201 publications
(138 reference statements)
4
243
0
5
Order By: Relevance
“…Host cells are instead 67 protected from AMP as they are positively charged and contain cholesterol 68 (Brender et al, 2012). In vitro studies have revealed AMPs capacity to kill 69 cancer cells (Deslouches and Di, 2017). However, whether this cancer-killing 70 activity is a natural function of AMPs is unknown, as there are no reports on 71 an in vivo paradigm addressing such question.…”
Section: Introduction 39mentioning
confidence: 99%
“…Host cells are instead 67 protected from AMP as they are positively charged and contain cholesterol 68 (Brender et al, 2012). In vitro studies have revealed AMPs capacity to kill 69 cancer cells (Deslouches and Di, 2017). However, whether this cancer-killing 70 activity is a natural function of AMPs is unknown, as there are no reports on 71 an in vivo paradigm addressing such question.…”
Section: Introduction 39mentioning
confidence: 99%
“…Pojęcie defensyny wprowadzono do literatury w 1985 r. [9]. Są to niewielkie peptydy (masa 3-5 kDa), których cząsteczki mają strukturę β-harmonijki i zawierają sześć reszt cysteiny, powiązanych trzema mostkami siarczkowymi [10]. Znanych jest już ponad 550 defensyn naturalnych [11,12].…”
Section: Defensynyunclassified
“…W przeciwieństwie do innych AMP, katelicydyny mają stosunkowo niską homologię domeny C-końcowej. Cząsteczki katelicydyn mają na ogół strukturę α-helisy złożonej z nie więcej niż 40 reszt aminokwasów, ale istnieją też przykłady o strukturze β-harmonijki (protegryna), cyklicznej (bektenecyna bydła), katelicydyny bogate w tryptofan (bydlęca indolicydyna, 13 reszt aminokwasów) lub w prolinę i argininę (katelicydyna OaBac owcy) [10].…”
Section: Katelicydynyunclassified
See 2 more Smart Citations